Experimentation of Basic Level BIPA Teaching Materials on Reading Proficiency at Islam Wittaya School - Ulfani, Ulfani; Febriyana, Mutia (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2025)
This study aims to analyse the effectiveness of the BIPA teaching material "Fluent Reading of Letter Combinations" in improving the reading skills of elementary-level students at Islam Wittaya School. The research employs a quantitative method with a quasi-experimental approach using a one-group pretest-posttest design. The sample consists of 10 students from class 3/1 Mattayom at Islam Wittaya School, selected through simple random sampling. Data were collected through reading proficiency tests and analyzed using descriptive and inferential statistics. The prerequisite tests included normality and homogeneity tests, while the hypothesis test was conducted using a paired sample t-test. The results indicate a significant improvement in students' reading skills after using the teaching material. The posttest mean score was higher than the pretest score, and the number of students who achieved the Proficient category increased. The normality and homogeneity tests confirmed the validity of the data distribution, while the t-test results showed a significant difference between the pretest and posttest scores. In conclusion, the BIPA teaching material "Fluent Reading of Letter Combinations" is effective in improving the reading skills of elementary-level BIPA students